Impression Management and Employee Commitment in Akwa-Ibom Tertiary Institutions: Manajemen Kesan dan Komitmen Karyawan di Institusi Tersier Akwa-Ibom - Agbonmwanre, Omorogieva Anthony (Universitas Muhammadiyah Sidoarjo, 2024)
General background: Employee commitment is crucial for organizational success, and impression management techniques may significantly influence this commitment. Specific background: Previous studies have examined the effects of impression management in organizational contexts, yet the specific dynamics in Nigerian tertiary institutions remain underexplored. Knowledge gap: The influence of exemplification, ingratiation, and self-promotion on different dimensions of employee commitment (affective, continuance, and normative) in Nigerian institutions has not been fully examined. Aims: This study aims to determine how these dimensions of impression management influence employee commitment and the moderating role of organizational culture. Results: Findings reveal a positive and significant relationship between impression management and employee commitment. Specifically, exemplification enhances affective commitment, ingratiation promotes continuance commitment, and self-promotion influences normative commitment. Organizational culture was found to strongly moderate these relationships. Novelty: This study provides new insights into the contextual effects of impression management on employee commitment in Nigerian tertiary institutions. Implications: The findings suggest that management should employ strategic impression management techniques to enhance employee commitment, fostering improved organizational performance and reduced turnover. Highlights: Impression management positively influences employee commitment in tertiary institutions. Exemplification enhances affective commitment, ingratiation promotes continuance commitment. Organizational culture strongly moderates the relationship between impression management and employee commitment. Keywords: Impression Management, Employment Commitment, Exemplification, Ingratiation, Self-Promotion